Climate change in Asia and the Pacific: challenges and perspectives - Lane, Jan-Erik; Dieterlen, Florent (2017)
The Asian Development Bank has presented a major report on the consequences for Asia and the Pacific of an ongoing global warming process, as exacerbated by more CO2 and other greenhouse gases such as methane. The Bank argues that countries in Asia and the Pacific contribute much to CO2 emissions and, consequently, have to share the burden of global coordination in the COP21 Treaty. It suggests the use of carbon capture, while recognising that huge investments in renewables are preferable. These are vital responses to the challenges involved, which are considered in this review article from the perspectives of global warming theory and global policy coordination. - Reproduced.
Keywords: Global warming theory; Climate change - Asia and Pacific; Climate change